A New Approach for Exploring Ice Sheets and Sub-Ice Geology - Eisen, Olaf; Hofstede, Coen; Miller, Heinrich; Kristoffersen, Yngve; Blenkner, Rick; Lambrecht, Astrid; Mayer, Christoph (Eos Transactions American Geophysical Union, 2010)
Keywords: Antarktis; geofysikk; geologi; innlandsis; seismologi

Comparison of elastic moduli from seismic diving-wave and ice-core microstructure analysis in Antarctic polar firn - Schlegel, Rebecca; Diez, Anja; Löwe, Henning; Mayer, Christoph; Lambrecht, Astrid; Freitag, Johannes; Miller, Heinrich; Hofstede, Coen; Eisen, Olaf (Annals of Glaciology, 2019)
We compared elastic moduli in polar firn derived from diving wave refraction seismic velocity analysis, firn-core density measurements and microstructure modelling based on firn-core data. The seismic data were obtained with a small electrodynamic vibrator source near Kohnen Station, East Antarctica. The analysis of diving waves resulted in velocity–depth profiles for different wave types (P-, SH- and SV-waves). Dynamic elastic moduli of firn were derived by combining P- and S-wave velocities and densities obtained from firn-core measurements. The structural finite-element method (FEM) was used to calculate the components of the elastic tensor from firn microstructure derived from X-ray tomography of firn-core samples at depths of 10, 42, 71 and 99 m, providing static elastic moduli. Shear and bulk moduli range from 0.39 to 2.42 GPa and 0.68 to 2.42 GPa, respectively. The elastic moduli from seismic observations and the structural FEM agree within 8.5% for the deepest achieved values at a depth of 71 m, and are within the uncertainty range. Our observations demonstrate that the elastic moduli of the firn can be consistently obtained from two independent methods which are based on dynamic (seismic) and static (tomography and FEM) observations, respectively, for deeper layers in the firn below ~10 m depth.
Keywords: Antarktis; glasiologi; seismologi